Screening and characterisation of bacteriophage P100 insensitive Listeria monocytogenes isolates in Austrian dairy plants. (January 2016) - Fister, S.; Fuchs, S.; Stessl, B.; Schoder, D.; Wagner, M.; Rossmanith, P.
Abstract: Listeria monocytogenes is a major health threat in food production premises. The use of bacteriophages, such as listeriaphage P100, to minimize food pathogens is a promising alternative to eliminate bacteria, as is application of Listex™ P100. However, the use of phages may result in resistant L. monocytogenes strains. In this study 486 L. monocytogenes isolates obtained from 59 dairies over 15 years were screened for the presence of P100 insensitive L. monocytogenes . The overall number of P100 insensitive L. monocytogenes isolates was 13 (2.7%) for all years and all investigated plants. Insensitivities were detected in five of 59 dairies. Detected insensitive isolates did not appear randomly, but were in connection with phage treatments. The influence of dilution on the efficacy of P100 was tested by different host pathogen ratios. Additionally, artificially induced insensitive isolates were selected. Adsorption tests suggested that the detected insensitive L. monocytogenes isolates had receptor modifications. Highlights: For the first time, Listeria monocytogenes insensitive to the phage P100 in dairy plants were investigated. Insensitive L. monocytogenes isolates were found only after the treatment with the phage P100 (as Listex™ preparation). Data indicate that improper use of Listex™ for control of L. monocytogenes can lead to resistance to P100.